Strontium and calcium isotopic data for bulk carbonate solids and pore fluids from ODP Sites 189-1170 and 189-1171 - Matthew S Fantle (PANGAEA, 2018)
Strontium and calcium isotopic data for bulk carbonate solids and pore fluids from ODP Sites 1170 and 1171 are presented. Bulk carbonate and pore fluid samples from Ocean Drilling Program (ODP) Sites 1170A and 1171A were measured in this study. Both sites are located on the South TasmanRise; Site 1170A (47°09.0435°S; 146°02.9881°E) was drilled in 2704.7 m water depth and Site 1171A (48°29.99600S;149°06.69010E) was drilled in 2148.2 m water depth. The tables provide summarized data.